Distinctive Expression of MetastamiRs in Breast Cancer Mesenchymal Stem Cells Isolated from Solid Tumor - Hashemi, Zahra S.; Moghadam, Mehdi Forouzandeh; Khalili, Saeed; Hashemi, Seyed Mahmoud; Sepehr, Koushan Sineh; Sadroddiny, Esmaeil (Current Stem Cell Research & Therapy, 2024)
Background: MSCs are a part of the tumor microenvironment, which secrete cytokines and chemokines. They can affect metastasis and the growth of tumors. metastamiRs are newly recognized regulatory elements of the metastasis pathway which are involved in epithelial-to-mesenchymal transition (EMT). Objective: In the present study, we aimed to assess the expression profile of metastamiRs in the context of MSCs in correlation with their invasion and migration power. Methods: Tumor-isolated BC-MSCs and normal human mammary epithelial cells (HMECs) along with MCF-7, MDA-MB231, and MCF-10A cells were prepared and confirmed for their identity. The cells were assessed for CD44+CD24¯ percentage, Oct-4, and Survivin expression. GEO, KEGG, and TCGA databases were investigated to detect differential miR-expressions. Real- time PCR for 13 miRs was performed using LNA primers. Ultimately, Transwell-Matrigel assays as used to assess the level of migration and invasion. Results: Our results indicated that some oncomiRs like miR-10b were upregulated in BC-MSCs, while the levels of miR-373 and miR-520c were similar to the MCF-10A. Generally, miR-200 family members were on lower levels compared to the other miR-suppressor (miR-146a, 146b, and 335). miR-31 and 193b were up-regulated in MCF-10A. The most invasiveness was observed in the MDA-MB231 cell line. Conclusion: We have demonstrated that the miR-expression levels of BC-MSCs are somewhat in between MCF-7 and MDA-MB231 miR-expression levels. This could be the logic behind the moderate level of invasion in BC-MSCs. Therefore, miR-therapy approaches such as miR-mimic or antagomiRs could be used for BC-MSCs in clinical cancer therapy.
Keywords: cancer stem cell